A Text-Linguistics Approach to the Literary Structure and Coherence of 2 Kings 17:7-23 - Lovell, Nathan (Vetus Testamentum, 2018)
This paper examines 2 Kgs 17:7-23 which is often understood as a fragmented text, compounding various theological reactions to the fall of Samaria. Applying a text-linguistics approach, I find vv7-20 to be a unit that makes sense in its present form, complementing a second unit beginning in v21. My reading understands the relationship between vv6 and 7 differently to what is usually understood, and to the standard English translations. I argue based on the Hebrew syntax that vv7-20 form a narrative unit that summarises the history of both northern and southern kingdoms together, as a history of idolatrous activity. Thus, the concern of the narrator is to explore the theological reason for the series of Assyrian invasions of the last quarter of the 8th Century bc, and the different fates of Israel and Judah.